The recession and migration: alternative scenarios - Martin, P (International Migration Institute, 2009)
The current recession, expected to be the worst in a generation, is likely to affect international migration and remittances differently than past recessions. In 1973-74 and 1981-82, a rise in oil prices was associated with recession in oil-buying countries and an economic boom in oil-exporting countries, enabling some migrants to shift destinations. The 1997-98 Asian financial crisis did not spread globally, and was followed by a relatively quick resumption of economic and job growth. The 2008-09 recession is most severe in sectors that hire relatively more migrant workers, including residential construction, light manufacturing, and financial and travel-related services. The major question is how severe this recession will be and whether migrants will remain abroad or return to their countries of origin.